Macrophages in AMD - Chan, Chi-Chao (Henry Stewart Talks, 2016)
Recruitment of macrophages, Changes in macrophages and their functions with age, Mechanisms of macrophage polarization in AMD, Macrophages and the complement system in AMD, The relationship between macrophages and inflammasomes, Alteration of macrophage activity for immune therapy of AMD